2022
DOI: 10.3390/jcm11092293
|View full text |Cite
|
Sign up to set email alerts
|

Resting State Functional Connectivity between Dorsal Attentional Network and Right Inferior Frontal Gyrus in Concussed and Control Adolescents

Abstract: Concussion among adolescents continues to be a public health concern. Yet, the differences in brain function between adolescents with a recent concussion and adolescents with no history of concussion are not well understood. Although resting state functional magnetic resonance imaging (fMRI) can be a useful tool in examining these differences, few studies have used this technique to examine concussion in adolescents. Here, we investigate the differences in the resting state functional connectivity of 52 adoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Moreover, the inferior frontal gyrus was found to be of special importance for inhibitory control of motor responses and impaired network integrity of the inferior frontal gyrus was related to vigorous physical activity ( Kullmann et al, 2014 ). Therefore, in study, increased nodal global efficiency in the left inferior frontal gyrus (opercular part), which had been shown to be crucial in the control of body movements ( Kullmann et al, 2014 ; Suss et al, 2022 ), might facilitate more efficient information transfer by greater functional connectivity with brain regions related to motor function in the brain (such as other areas of the frontal lobe, precentral and postcentral gyrus, somatosensory cortex) of male rowing athletes received tDCS.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, the inferior frontal gyrus was found to be of special importance for inhibitory control of motor responses and impaired network integrity of the inferior frontal gyrus was related to vigorous physical activity ( Kullmann et al, 2014 ). Therefore, in study, increased nodal global efficiency in the left inferior frontal gyrus (opercular part), which had been shown to be crucial in the control of body movements ( Kullmann et al, 2014 ; Suss et al, 2022 ), might facilitate more efficient information transfer by greater functional connectivity with brain regions related to motor function in the brain (such as other areas of the frontal lobe, precentral and postcentral gyrus, somatosensory cortex) of male rowing athletes received tDCS.…”
Section: Discussionmentioning
confidence: 98%
“…In our study, the inability to activate the LIFG for the 2-back condition was associated with slower RT and lower accuracy in concussed adolescents in the subacute period. Our previous resting-state functional connectivity study indicated that unlike HC showing connectivity between the IFG and dorsal attention network, concussed adolescents demonstrated no such connectivity [44]. Disconnection of the IFG from the attentional network may serve to avoid a ‘chain reaction’ and, consequently, more massive cognitive impairments when the IFG becomes dysfunctional.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the inability to activate the LIFG for the two-back condition was associated with a slower RT and lower accuracy in concussed adolescents in the subacute period. Our previous resting-state functional connectivity study indicated that unlike HCs showing connectivity between the IFG and dorsal attention network, concussed adolescents demonstrated no such connectivity [ 47 ]. Disconnection of the IFG from the attentional network may serve to avoid a ‘chain reaction’ and, consequently, more massive cognitive impairments when the IFG becomes dysfunctional.…”
Section: Discussionmentioning
confidence: 99%